How different are rape trials? A comparison of the cross-examination of complainants in rape and assault trials - Brereton, David (The British journal of criminology, 1997)
A common theme in the literature on rape trials is that complainants in such cases are routinely subjected to forms of questioning by defence counsel that would rarely, if ever, be utilized in other trial contexts. This paper critically examines this assumption, drawing upon a comparative study of transcripts of assault and rape trials conducted in the Melbourne County Court between 1989 and 1991. The paper concludes that, while the rape trials undoubtedly had some unique features, there were also strong similarities in the way in which complainants in the two types of trials were cross-examined. These findings suggest that a proper understanding of rape trials can only be obtained through comparative analysis, and by giving due explanatory weight to factors such as the constraints imposed by adversarial processes and structures, the structure and logic of legal language and techniques, and the assumptions which lawyers and judges make about what is relevant evidence